Do Prostaglandin Analogue Lash Lengtheners Cause Eyelid Fat and Volume Loss?. (14th June 2022) - Jamison, Aaron; Okafor, Linda; Ullrich, Katja; Schiedler, Vivian; Malhotra, Raman
Abstract: Background: Prostaglandin analogues (PGAs; a first-line antiglaucoma treatment) have been remarketed as popular eyelash-lengthening serums due to their lash-lengthening and lash-thickening side effects. Periorbital volume loss is now a well-established side effect of topical PGAs used to treat glaucoma (prostaglandin-associated periorbitopathy) but has not, to date, been listed as a potential side effect of lash-lengthening serums containing PGAs. Objectives: The aim of this study was to identify whether periorbital fat/volume loss is seen in users of PGA lash lengtheners. Methods: This investigation comprised a case report and an informal randomized controlled study comparing "before-and-after" color photographs displayed on the websites of manufacturers of PGA-containing lash lengtheners (PGALLs) (ie, containing bimatoprost, norbimatoprost, isopropyl cloprostenate, dechloro-dihydroxy-difluoro-ethylcloprostenolamide, or methylamido-dihydro-noralfaprostal) vs 2 control groups: non-PGALLs (NPGALL) and false eyelashes (FLs). Expert and layperson blinded graders used a purpose-designed grading system to identify subtle signs of periorbital fat/volume loss over time. Results: A 35-year-old female developed thin, wrinkled, darker skin, and periorbital hollowing after 10 months of treatment with Lash Boost (Rodan & Fields, San Francisco, CA), containing isopropyl cloprostenate, which reversed 6 months after discontinuation. Fifteen "before-and-after" pairs of photographs (PGALL, n = 10; NPGALL, n = 3; FL, n = 2) were graded by 5 graders (3 expert, 2 layperson). Mean grading score was 8.2 (of 19) in the PGALL group, 2.3 in the NPGALL group, and 3.2 in the FL group. PGALL scores were significantly higher than scores in the NPGALL ( P  < 0.001) and FL ( P  = 0.017) groups. Conclusions: Review of commercial "before-and-after" photographs suggests that PGALL users develop changes compatible with prostaglandin-associated periorbitopathy. Consumers must be aware of the possibility of periorbital volume loss prior to commencing treatment with PGALLs. Often the customer-facing product ingredient list contains no mention of PGAs. Level of Evidence: 4: